Supine Bottom-Up Extralevator Abdominoperineal Excision With Primary Perineal Approach. Issue 7 (July 2018) - de Chaisemartin, Cécile; Mège, Diane; Durey, Jean Michel; Meillat, Hélène; Delpero, Jean Robert; Lelong, Bernard
Abstract : Supplemental Digital Content is available in the text.